Mental health levels in hysterectomised women: A Study of Trauma and Depression in Setif, Algeria - DERGUINI, Said Mehdi; Bensalhia, Karima; Sakina, Daksi; BOUDJERADA, Mohamed (The International tax journal, 2025)
This study explores the mental health levels of women who have undergone hysterectomy, focusing on symptoms of psychological trauma and depression. A sample of 50 hysterectomised women from Setif, Algeria, was selected to assess their mental health using two standardized scales: the Psychological Trauma Scale and the Beck Depression Scale. The study employed a descriptive, analytical, and evaluative methodology to understand the severity of trauma and depression in this group and examine the relationship between these two factors. The findings reveal that hysterectomised women experience moderate levels of psychological trauma (mean = 2.5353, SD = 1.126) and low levels of depression (mean = 1.2714, SD = 0.620). Moreover, a strong positive correlation was found between trauma symptoms and depression (Spearman Brown correlation = 0.625, p < 0.05), suggesting that higher trauma symptoms are associated with greater depression. However, no significant differences were observed in trauma or depression levels based on age groups, which indicates that age may not play a significant role in these variables for hysterectomised women. These findings contribute to the understanding of the psychological challenges faced by hysterectomised women, in relation to trauma and depression, and provide insights for healthcare providers and counselors working with this population.